1990
DOI: 10.1128/mcb.10.3.1084
|View full text |Cite
|
Sign up to set email alerts
|

Stable transfection of the human parasite Leishmania major delineates a 30-kilobase region sufficient for extrachromosomal replication and expression.

Abstract: To delineate segments of the genome of the human protozoan parasite Leishmania major necessary for replication and expression, we developed a vector (pR-NEO) which can be reproducibly introduced into L. major. This DNA was derived from a 30-kilobase extrachromosomal amplified DNA bearing the dihydrofolate reductase-thymidylate synthase gene, with the coding region for neomycin phosphotransferase substituted for that of dihydrofolate reductase-thymidylate synthase and a bacterial origin of replication and selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
299
0
16

Year Published

1990
1990
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(318 citation statements)
references
References 45 publications
3
299
0
16
Order By: Relevance
“…Parasite numbers were determined using a Coulter counter as previously described after an incubation of 2 days for the amastigotes and 3 days for the promastigotes. The effective concentration for 50% inhibition (EC 50 ) was defined as that drug concentration that resulted in a 50% decrease in cell number, measured at the time when control cultures lacking drug had reached 10 7 /ml [21].…”
Section: Leishmania Culture and Differentiation In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…Parasite numbers were determined using a Coulter counter as previously described after an incubation of 2 days for the amastigotes and 3 days for the promastigotes. The effective concentration for 50% inhibition (EC 50 ) was defined as that drug concentration that resulted in a 50% decrease in cell number, measured at the time when control cultures lacking drug had reached 10 7 /ml [21].…”
Section: Leishmania Culture and Differentiation In Vitromentioning
confidence: 99%
“…Analysis of LPG expression showed that in general the primary transfectants did not make normal levels of LPG, for unknown reasons. Since episomal expression can be elevated by increasing the copy number [21], we used a combined FACS/drug selection protocol to recover parasites showing wild-type LPG expression. One clonal line (clone 2) of the primary lpg2 − /pSNBR-LmLPG2 transfectants was labeled with FITC-ricin, and the 5% of cells showing the most intense labeling were recovered by flow cytometry, and inoculated into 10-80 g/ml G418 in the presence of 2% galactose (first passage only).…”
Section: Generation Of An Lpg2 − Null Mutant By Transfection and Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Promastigotes were grown in M199 medium supplemented as described [11,22]. Parasites from late log phase cultures were transfected by electroporation (500 F, 2.25 kV/cm) using 20-40 g of cosmid DNA.…”
Section: Parasites Cultures Transfections and Drugsmentioning
confidence: 99%
“…Transfection of Leishmania with foreign genes has been reported both transiently (11) and stably (12,13 (16) supplemented with 5% fetal bovine serum and 1% fresh, filter-sterilized human urine (17).…”
mentioning
confidence: 99%